Sistem Tiket Pengadian Berbasis Case-Based Reasoning Untuk Meningkatkan Pelayanan Pengaduan - Arpan Dadi (Universitas Bandar Lampung (UBL), 2012)
With the technological use growth of computer as a means of assist in finishing work in company which progressively mount fast, what do not in .following behaviorally is good in using computer technology, and its minimize is human resource which with quality vertalis in a company, will be happened by the delay in course of accurate and is not solution in finishing solution. System of Case-Based Reasoning (CBR) that is technique of is solving of problem of pursuant to Case-Based of passing process Retrieve, Reuse,Revise, Retain to be formed by new knowledge in course of solving of solution. Applying CBR have a lot of weared in solution seeking by exploiting or previous prosescase data. CBR own five duty in forming knowledge that is case representation, case Index, case retrieval, case adaptation, and case maintenance. At case adaptation represent the process of case seeking which own of speed and accuracy in seeking of new case-based and knowledge, at system of solution ticket. This research to explain about applying CBR in system of solution ticket to process the solving of solution quickly and accurate. Where process of inclusion knowledge represent the important step in course of solving ofsolution ticket